Past, present, and future of palliative care in emergency medicine in the USA. Issue 1 (18th March 2020) - George, Naomi; Bowman, Jason; Aaronson, Emily; Ouchi, Kei
Abstract : The emergency department (ED) provides immediate access to medical care for patients and families in times of need. Increasingly, older patients with serious illness seek care in the ED, hoping for relief from symptoms and suffering associated with advanced disease. Until recently, emergency medicine (EM) clinicians have been ill‐equipped to meet the needs of patients with serious illness, and palliative services have been largely unavailable in the ED. However, in the past decade, there has been growing recognition from within both the EM and palliative medicine communities on the importance of palliative care provision in the ED. The past 10 years have seen a surge in EM–palliative care training and education, quality improvement projects, and research. As a result, the practice paradigm within EM for the seriously ill has begun to shift to incorporate more palliative care practices. Despite this progress, substantial work has yet to be done in terms of identifying ED patients in need of palliative care, training EM clinicians to provide high‐quality primary palliative care, creating pathways for ED referral to palliative care and hospice, and researching the outcomes and impact of palliative care provision on patients with serious illness in the ED. Abstract : To meet the growing needs of older adults with serious illness in the emergency department, changes are steadily occurring in the practice of emergency medicine in the USA to incorporate palliative care.